PENGARUH TERAPI AKTIVITAS KELOMPOK STIMULASI SENSORI TERHADAP GANGGUAN PSIKOSOSIAL LANJUT USIA DI BALAI PENYANTUNAN LANJUT USIA SENJA CERAH MANADO - Monica S. Tandiayuk (Jurnal Ilmiah Perawat Manado (Juiperdo), 2013)
Old process in journey of human life represent fair a letter to experiencing of every person who is bestowing longevity, only tardy quikly it the process base on the each pertinent individual. Individually, happened process of aging naturally. This matter will generate the problem of physical, bouncing, social, psychological an economic. Psychological problem that happened continuing age one of them trouble of psychosocial. Trouble of psychosocial natural continue age like depend on others, self insulation or with draw from activity of social. Target of this research is to identify group activity therapy of stimulation censori, identifying trouble of psychosocial continue age and to know influence of group activity therapy of stimulation censori to trouble of psychosocial continue age. This research type use device of quasi design experimental. Non design group control equivalent with technique in take of sampel that is sampling purposive to 20 divided into responder 10 lansia for the group of experiment an 10 lansia for the group of control. Technique data collecting trough interview and observation. Data processing use SPSS version computer 16. Result of research through result of test of variance (Anava) got by value for the group of eksperiment – 2,800 with mistake level 0,05 and trust storey level 95 % hence f value = 0.000 < 0,05. While at control group assess f = 0,000 wit mistake level 0,05 and trust storey level 95 % hence f value = 1,000 > 0,05. By comparing capacities value test two side mean p niali for the group of experiment < assess p control group. So that comparison of this value can be told is ha accepted and Ho refused. Become there is influence of group activity therapy of stimulation censori to trouble of psychosocial continue age in decent hall continue fair dusk age of manado